2021
DOI: 10.1080/25765299.2021.1975403
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional evaluation of the effects of Ramadan intermittent fasting on the health of female students at the University of Bahrain

Abstract: This research aimed to assess the effects of Ramadan intermittent fasting (RIF) on different dimensions, namely calorie intake, fullness and hunger sensations, mental health, body weight, waist circumference (WC), quality of sleep, body composition, hydration and nutritional status among female students at the University of Bahrain. A prospective single cohort study was conducted on 20 female students. The measurements were taken before Ramadan as well as the end of each week of Ramadan. From baseline to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The authors found no significant effect of Ramadan fasting on sleep quality in healthy individuals. A similar result was observed in female healthy students from Bahrain ( 62 ). Alzhrani et al ( 140 ) reported that sleep duration remained unchanged from before to during Ramadan in 115 adults (96 females and 19 males) form Saudi Arabia.…”
Section: Religious Fasting Nutrition and Individual Healthsupporting
confidence: 86%
See 2 more Smart Citations
“…The authors found no significant effect of Ramadan fasting on sleep quality in healthy individuals. A similar result was observed in female healthy students from Bahrain ( 62 ). Alzhrani et al ( 140 ) reported that sleep duration remained unchanged from before to during Ramadan in 115 adults (96 females and 19 males) form Saudi Arabia.…”
Section: Religious Fasting Nutrition and Individual Healthsupporting
confidence: 86%
“…Hasan et al ( 61 ) found that Ramadan fasting decreased BMI and waist circumference in 55 overweight and obese participants (22 females and 33 males). Alsowaid et al ( 62 ) enrolled only female individuals ( n = 20) who were healthy students at the University of Bahrain. The authors found that Ramadan fasting decreased body mass, BMI, fat mass, and waist circumference ( 62 ).…”
Section: Religious Fasting Nutrition and Individual Healthmentioning
confidence: 99%
See 1 more Smart Citation